2022
DOI: 10.48156/1388.2022.1917169
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation of prementum size in Iberian Cordulegaster boltonii (Odonata: Cordulegastridae) populations

Abstract: Within wide geographical areas, Odonata populations can show biometric differences as a consequence of both biotic (e.g., predation, competition) and abiotic factors (mainly temperature). These differences can occur in the larval stage, although reliable characters are needed to detect differences. We analyzed whether Cordulegaster boltonii larvae from 18 Iberian populations differ regarding head width and prementum size (maximum width, minimum width, and maximum length), using measurements taken on final stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…Previous works have demonstrated that males and females of Iberian C. boltonii differ in larval biometry (Casanueva et al, 2020;Ferreras-Romero & Corbet, 1999). Females are larger in size than of males in both larvae and F-0 larva exuviae (Hernández et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous works have demonstrated that males and females of Iberian C. boltonii differ in larval biometry (Casanueva et al, 2020;Ferreras-Romero & Corbet, 1999). Females are larger in size than of males in both larvae and F-0 larva exuviae (Hernández et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Within the Iberian Peninsula, the sizes of some C. boltonii structures vary with the geographical situation of the individual populations. Indeed, the prementum sizes of F-0 exuviae are greater in southern populations than in northern ones, in both males and females (Hernández et al, 2022). El Haissoufi et al (2018 and Casanueva et al (2020) analyzed head width in exuviae of F-0 larvae (only females) from Iberia and North Africa and showed that those from the Rif Mountains (Morocco) are clearly larger than those inhabiting the Iberian Peninsula.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, head width has been used in recent studies on Cordulegaster boltonii (Donovan, 1807) and B. irene exuviae (Casanueva et al . 2020; Nunes et al 2021a; Hernández et al 2022).…”
Section: Methodsmentioning
confidence: 99%